A Super Wideband Directional Compact Vivaldi Antenna for Lower 5G and Satellite Applications - Liton Chandra Paul; Md. Mohiminul Islam (International Journal of Antennas and Propagation)
In this paper, a super wide band (SWB) Vivaldi antenna has been proposed for lower 5G bands in Sub-6 GHz and satellite applications (S, C, X, Ku, and K band) using various performance improvement techniques. In the presented Vivaldi antenna, different slots are applied not only to increase the gain and directivity but also to get operating frequency at the intended specific frequency range. All dimensions of those slots were chosen by using the sweep parameter method. Ten corrugated side slots, two circular slots, and one via have been used to enhance the performance especially bandwidth and gain of the antenna. At the edge of wireless communication, we want to enhance two key aspects within the communication systems: the quality of service and the cost. The proposed antenna incorporates a simple structure and small size with dimensions of 45 × 35 × 0.79 mm3. Thus, after design, optimization, and simulation, the antenna produces a good reflection coefficient over the very large operating bandwidth of 23.19 GHz, 1 < VSWR < 2, maximum gain of 10.2 dBi, and average radiation efficiency of above 90%, which can be recommended as a suitable antenna for lower 5G as well as satellite applications. The antenna is designed, simulated, and analyzed by using computer simulation technology microwave studio (CST-MWS). Finally, the performance of the Vivaldi antenna has been validated by FEKO and HFSS software, and we achieved a very good matching among the results.